Geographic Information System (GIS) as an Information Media in the Field of Environmental Health: Literature Review - Maghfirah Dara Chaniago; Herika Muhamad Taki (Politeknik Negeri Batam, 2022)
Geographic Information System (GIS) is a system with a collection of data that has a special capacity to combine data, coordinate data, and perform data checks that produce output to be used as a source of decision making. Geographic Information Systems (GIS) can be linked to health information at a particular location, combine, analyze and produce the health information according to activities in the health sector per location. Furthermore, the use of Geographic Information Systems (GIS) is planned to determine areas, conditions, styles, patterns and models related to the health sector. Geographic Information System (GIS) can create a map display by knowing the data from the map and other related data in presenting information about an area on the map.